COMPREHENSIVE ANALYSIS OF RISK FACTORS FOR CAROTID PLAQUE IN TYPE 2 DIABETES MELLITUS: A META-ANALYSIS - Yang, Wei Liang (Global Journal of Medical and Health Science, 2023)
Type 2 diabetes mellitus (T2DM) is a global health concern with a rising incidence and severe complications. Carotid plaque formation, indicative of diabetic macrovascular complications, serves as a significant predictor of cardiovascular and cerebrovascular diseases. This study conducts a comprehensive meta-analysis of risk factors contributing to carotid plaque formation in individuals with T2DM, aiming to provide valuable insights and a solid theoretical foundation for future research and intervention strategies. The increasing prevalence of T2DM makes understanding and addressing carotid plaque formation imperative to reduce the risk of cardiovascular morbidity and mortality.